Impact of uric acid on liver injury and intestinal permeability following resuscitated hemorrhagic shock in rats. Issue 6 (December 2020) - Khazoom, François; L'Écuyer, Sydnée; Gilbert, Kim; Gagné, Marc-André; Bouchard, Caroline; Rose, Christopher F.; Rousseau, Guy; Charbonney, Emmanuel
Abstract : BACKGROUND: Multiorgan failure is a consequence of severe ischemia-reperfusion injury after traumatic hemorrhagic shock (HS), a major cause of mortality in trauma patients. Circulating uric acid (UA), released from cell lysis, is known to activate proinflammatory and proapoptotic pathways and has been associated with poor clinical outcomes among critically ill patients. Our group has recently shown a mediator role for UA in kidney and lung injury, but its role in liver and enteric damage after HS remains undefined. Therefore, the objective of this study was to evaluate the role of UA on liver and enteric injury after resuscitated HS. METHODS: A murine model of resuscitated HS was treated during resuscitation with a recombinant uricase, a urate oxidase enzyme (rasburicase; Sanofi-Aventis, Canada Inc, Laval, Canada), to metabolize and reduce circulating UA. Biochemical analyses (liver enzymes, liver apoptotic, and inflammatory markers) were performed at 24 hours and 72 hours after HS. Physiological testing for enteric permeability and gut bacterial product translocation measurement (plasma endotoxin) were performed 72 hours after HS. In vitro, HT-29 cells were exposed to UA, and the expression of intercellular adhesion proteins (ZO-1, E-cadherin) was measured to evaluate the influence of UA on enteric permeability. RESULTS: The addition of uricase to resuscitation significantly reduced circulating and liver UA levels after HS. It also prevented HS-induced hepatolysis and liver apoptotic/inflammatory mediators at 24 hours and 72 hours. Hemorrhagic shock–induced enteric hyperpermeability and endotoxemia were prevented with uricase. CONCLUSIONS: After resuscitated HS, UA is an important mediator in liver and enteric injury. Uric acid represents a therapeutic target to minimize organ damage in polytrauma patients sustaining HS. Abstract : Supplemental digital content is available in the text.